The optimal capital structure of Swiss dairy farms. Issue 3 (3rd June 2019) - Schorr, Anke; Lips, Markus
Abstract : Purpose: The purpose of this paper is to propose a novel way of determining optimal capital structure, applied to sub-groups of Swiss dairy farms from 2003 to 2014. Optimization of capital structure is carried out with respect to two performance indicators from an economic value added perspective. Design/methodology/approach: Optimal values of capital structure are obtained based on a minimization of correlation between economic performance indicators and a distance function of the debt-to-asset ratio distribution to its quantiles. The approach differs from existing approaches in relying solely on empirical data and in using fewer external parameters, which are difficult to estimate, such as risk aversion coefficients. An unbalanced panel data set from the Swiss Farm Accounting Network with almost 14, 000 dairy farm observations serves as input data to the model. Findings: Concise optimal values of capital structure result for regional and temporal sub-groups of Swiss dairy farms. Comparing the evolution of optimal values for these sub-groups with existing models of optimal capital structure, the authors infer that dairy farmers in the mountain region are less risk averse than their counterparts in the valley region and that falling interest rates increase the optimal value of debt-to-asset ratio. Originality/value: The straightforward computation of optimal values for capital structure without intermediate parameters is useful and new. In addition, the authors' model can be used as a tool for comparison and validation of previous models with the same aim, e.g. for comparison of risk aversion coefficients or qualitative behavior of optimal values for capital structure.